Comparison of Dapoxetine /Tadalafil and Paroxetine/Tadalafil Combination Therapies for the Treatment of the Premature Ejaculation: A Randomized Clinical Trial: Combination therapy of Dapoxetine and Paroxetine - Mohseni Rad, Hamed; Zahirian Moghadam, Telma; Hosseinkhani, Ali; Nima Soluki, Nima; Amani, Firouz (Urology Journal, 2021)
Purpose: The purpose of this study was to compare the effectiveness of Dapoxetine, and Paroxetine as well as Dapoxetine/Tadalafil and Paroxetine/Tadalafil combinational therapies, for the treatment of patients with premature ejaculation. Materials and Methods: In this clinical trial study, 120 patients with premature ejaculation were randomly divided into 4 groups: The first group was treated with Paroxetine (Pa), while the second group received Dapoxetine(Da). The third group received Paroxetine combined with Tadalafil(PT) whereas the fourth group's treatment involved the use of Dapoxetine and Tadalafil(DT) for one month. In the next 2 and 4 weeks, the cases were evaluated in terms of ejaculation duration, frequency of intercourse per week, and drug side effects. Results: The mean age of the Da, Pa, PT, DT groups was 32 ± 6.9, 32.4 ± 7.2, 31.6 ± 1.9, and 32.9 ± 7.7 years, respectively. There was a significant difference between the Da and DT groups (p = .029) in the ejaculation latency in the 4-week follow-up. In the two weeks follow-up, a significant difference was observed between DA and DT (p = 0.043), Pa and PT (p = 0.006), and Pa and DT groups (p = 0.004) in terms of ejaculation latency. Four weeks after the intervention, a significant difference was detected in the intercourse frequency of Da and PT groups (p =0.033), Pa and PT groups (p = 0.043), Pa and DT groups (p = 0.02), and Da and DT groups (p = 0.016). Conclusion: Combination therapy (Tadalafil plus Paroxetine or Dapoxetine) was more effective in IELT (Intra ejaculation latency time) than mono-therapy especially in younger patients despite its slightly more side effects.